Nemeth in a Box: Unpacking Tools to Build Success in Math for Students with Visual Impairments - Herzberg, Tina; Wild, Tiffany; Rosenblum, L. Penny (Ohio Journal of School Mathematics, 2023)
Students with visual impairments can be successful in math learning if they are provided with accessible materials, appropriate accommodations, and knowledgeable teachers. Four teachers of students with visual impairment designed a set of activities to build middle school students' knowledge of the braille code while engaging in math activities. The activities are described, and the authors provide strategies for successfully including students in general education math classes.